Podium Podcast and the freedom of podcasting: Beyond the limits of radio programming and production constraints. (1st April 2019) - Sellas, Toni; Solà, Sergi
The evolution of the Internet and the impact of digitalization have led the radio industry to try new production, distribution and commercialization strategies. In Spain, radio on the Internet began in the mid-1990s, and years later, in 2005, broadcasters incorporated podcasting. For more than a decade, they have used podcasts as a distribution tool, but in recent years, they have started to offer new content through podcasting. In June 2016, PRISA, one of the main Spanish media groups, took a step further with the launch of Podium Podcast. It is a new brand and platform, with a specific catalogue of native podcasts created and delivered taking podcast listeners into account. Podium Podcast is part of PRISA's digital strategy, but it also shows a new approach to podcasting by the radio industry. Podcasters in Podium Podcast feel free of radio programming conventions and have the opportunity to experiment with content that does not fit into current radio stations' schedules. Podium Podcast expands the Spanish podcasting sphere and contributes to the popularization of podcasts. However, we wonder to what extent it is a threat to independent podcasters and if it might contribute to the colonization of the field by the mainstream.